2019
DOI: 10.1016/j.anai.2018.12.012
|View full text |Cite
|
Sign up to set email alerts
|

The gut microbiome in food allergy

Abstract: Growing evidence supports a role for the gut microbiome in the pathogenesis and course of food allergy. Gut dysbiosis may precede the development of food allergy, and the timing of such dysbiosis is critical. Gut microbiota associated with individual food allergies may be distinct. Murine models suggest that gut microbiota affect food allergy susceptibility by modulating type 2 immunity, influencing immune maturation and tolerance, regulating basophil populations, and promoting intestinal barrier function. Ong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
77
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(88 citation statements)
references
References 65 publications
0
77
0
2
Order By: Relevance
“…Alternatively, cocktails of protective bacterial strains, including Clostridiales or Bacteroidales strains, such as B fragilis, could also be considered in protection from FA. Probiotic supplementation with Lactobacillus rhamnosus GG has been utilized during OIT for peanut allergy, and prebiotics, including oligofructose, acidic oligosaccharides, and long-chain inulin, in combination with the prebiotic Bifidobacterium breve M-16V, have also been administered in clinical trials for FA with some success [165][166][167][168][169][170][171][172][173].…”
Section: Pharmacological Treatmentsmentioning
confidence: 99%
“…Alternatively, cocktails of protective bacterial strains, including Clostridiales or Bacteroidales strains, such as B fragilis, could also be considered in protection from FA. Probiotic supplementation with Lactobacillus rhamnosus GG has been utilized during OIT for peanut allergy, and prebiotics, including oligofructose, acidic oligosaccharides, and long-chain inulin, in combination with the prebiotic Bifidobacterium breve M-16V, have also been administered in clinical trials for FA with some success [165][166][167][168][169][170][171][172][173].…”
Section: Pharmacological Treatmentsmentioning
confidence: 99%
“…Food intolerance due to dysbiosis is also reported by numerous authors [11][12][13]. Asthma is a condition frequently considered due to alterations suffered by the microbiota [14][15][16].…”
mentioning
confidence: 84%
“…33 Thus, it is not surprising that several investigators have reported an association between decreased gut microbial diversity, and in some cases specific microbial signatures, and food allergy. 34 Two recent studies employed fecal microbial transplants (FMT) from humans into germ-free mice and compared outcomes when the FMT was derived from foodallergic or healthy subjects. Feehley et al 28 found that FMT from healthy infants, but not from infants with cow's milk allergy, could suppress immunoglobulin E (IgE) induction and anaphylaxis in a model using b-lactoglobulin sensitization and challenge.…”
Section: Recent Insights Into Food Allergymentioning
confidence: 99%